2007
DOI: 10.1186/1471-2180-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Importance of c-Type cytochromes for U(VI) reduction by Geobacter sulfurreducens

Abstract: Background: In order to study the mechanism of U(VI) reduction, the effect of deleting c-type cytochrome genes on the capacity of Geobacter sulfurreducens to reduce U(VI) with acetate serving as the electron donor was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
166
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 52 publications
4
166
0
1
Order By: Relevance
“…The chemical composition of the medium can influence the nature of the reduced U mineral (34). We used a bicarbonate buffer and conditions used in previous studies with G. sulfurreducens (13), whereas studies reporting uraninite formation used PIPES-buffered solutions (36) or bicarbonatebuffered uncontaminated groundwater (10). Evidence for the microbial reduction of U(VI) to nonuraninite U(IV) products is also emerging from field-scale studies (35,37), whereas uraninite formation has been linked to conditions of reduced bioreducing activities (38,39); this suggests that abiotic factors may contribute to the formation of uraninite.…”
Section: Discussion Physiological Relevance Of the Extracellular Redumentioning
confidence: 99%
See 4 more Smart Citations
“…The chemical composition of the medium can influence the nature of the reduced U mineral (34). We used a bicarbonate buffer and conditions used in previous studies with G. sulfurreducens (13), whereas studies reporting uraninite formation used PIPES-buffered solutions (36) or bicarbonatebuffered uncontaminated groundwater (10). Evidence for the microbial reduction of U(VI) to nonuraninite U(IV) products is also emerging from field-scale studies (35,37), whereas uraninite formation has been linked to conditions of reduced bioreducing activities (38,39); this suggests that abiotic factors may contribute to the formation of uraninite.…”
Section: Discussion Physiological Relevance Of the Extracellular Redumentioning
confidence: 99%
“…However, mutations were often pleitrophic (14-16) and showed either no defect or only partial defects in the cell's ability to remove U(VI) (12,13). Interpretation was also difficult due to inconsistencies in the reported mutant phenotypes, with some mutations reportedly abolishing U(VI) removal activities, yet mutant cells showing extensive mineralization (13). Furthermore, these studies consistently showed that the U precipitated inside the cell envelope.…”
mentioning
confidence: 90%
See 3 more Smart Citations